Coxiella burnetii lipopolysaccharide blocks p38α-MAPK activation through the disruption of TLR-2 and TLR-4 association - Conti, Filippo; Boucherit, Nicolas; Baldassarre, Veronica; Trouplin, Virginie; Toman, Rudolf; Mottola, Giovanna; Mege, Jean-Louis; Ghigo, Eric (Frontiers in Cellular and Infection Microbiology, 2015)
To survive in macrophages, Coxiella burnetii hijacks the activation pathway of macrophages. Recently, we have demonstrated that C. burnetii, via its lipopolysaccharide (LPS), avoids the activation of p38α-MAPK through an antagonistic engagement of Toll-like receptor (TLR)-4. We investigated the fine-tuned mechanism leading to the absence of activation of the p38α-MAPK despite TLR-4 engagement. In macrophages challenged with LPS from the avirulent variants of C. burnetii, TLR-4 and TLR-2 co-immunoprecipitated. This association was absent in cells challenged by the LPS of pathogenic C. burnetii. The disruption makes TLRs unable to signal during the recognition of the LPS of pathogenic C. burnetii. The disruption of TLR-2 and TLR-4 was induced by the re-organization of the macrophage cytoskeleton by C. burnetii LPS. Interestingly, blocking the actin cytoskeleton re-organization relieved the disruption of the association TLR-2/TLR-4 by pathogenic C. burnetii and rescued the p38α-MAPK activation by C. burnetii. We elucidated an unexpected mechanism allowing pathogenic C. burnetii to avoid macrophage activation by the disruption of the TLR-2 and TLR-4 association.